Listening journals to promote students’ critical thinking skills in an integrated Listening-Speaking Course - Rina Astuti Purnamaningwulan (Studies in English Language and Education, 2022)
This study aims to explore whether there is a significant improvement in students’ critical thinking (CT) skills after implementing listening journals as one of the tasks in the Critical Listening and Speaking II course. This study also reports students’ responses to the implementation of listening journals. In this mixed-method study, students’ CT skill was measured using a Critical Thinking Self-Assessment (CTSA) Scale prior to and subsequent to the listening journal implementation period. Meanwhile, a reflective questionnaire with open-ended questions was employed to reveal students’ responses to the implementation of the listening journals’ tasks. Fifty students studying in the fourth semester of an English education department in a private university in Indonesia participated in this study. A paired-samples t-test result suggested a significant improvement in students’ scores from the pre- to the post- CT self-assessment (t = -4.136, p .05). In addition, the qualitative data obtained from the reflective questionnaire showed that the dominant responses from the students were positive towards the listening journal task. The findings of this study suggest that listening journals can be an effective strategy to help foster learners’ critical thinking while developing listening and other skills. Even so, some felt the process was too monotonous and difficult. Thus, suggestions for future research are offered to improve the journal’s future design and implementations.